The Role of the "New Cold War" Concept in Constructing Russia's Great Power Narrative - Ionela Maria Ciolan (CES Working Papers, 2016)
For the past two years, since the annexation of Crimea (2014), there is strong evidence to confirm that the relations between the West and Moscow have deteriorated. As conflicts are unfolding both in Eastern Europe and the Middle East, the tensions between the United States and Russia are at their highest point since the end of Cold War. In this context, the concept of “New Cold War” started to be more frequently used in Western media and think tank analyses, but also in Russian high officials' discourses. The concept was frequently used as a metaphor in public discourse with various tensed occasions in the last 2 decades. But it was most frequently used after the events in Ukraine. The main purpose of the article is to investigate the present context in which this concept is being used in relation with the main premises of Russian foreign policy. We are initializing our research with our research question: “How the “New Cold War” concept fosters the idea of the Russian Federation as a great power?”. This paper argues that the “New Cold War” is a symbolic concept used to strengthen Russia's great power narrative. Using constructivists' arguments of the international relations theory, we will examine this idea and will observe how this social construct helps Russia to strengthen its great power and offers a new interpretation to the international environment.
Keywords: 330; Russia; New Cold War; Great Power narrative; Socialization; foreign policy